Dog behaviour and ethology - Agostinho, Fábio Faustino (2022)
Dogs engage in various interactions with artificial agents (UMOs) but it is not clear whether they recognize UMOs as social agents. Jealous behaviour emerges when an important relationship is threatened by another individual, but only when the intruder is a social agent. We investigated whether UMOs elicit jealous behaviour in dogs. We tested three groups of 15 dogs, each group observed different behaviour of the UMO: mechanistic movement, non-social or social behaviour. Then, the owner interacted with another dog, the UMO and a magazine while ignoring the subject. Dogs displayed more rival-oriented behaviour and attempt to interrupt the owner-rival interaction in case of the other dog and UMO compared to the magazine (the latter mainly occurred in the Social UMO group). However, they showed less owner- and interaction-oriented behaviour in case of the UMO. Thus, although some elements of jealous behaviour emerged toward the UMO, the results are not conclusive; Resumo: Comportamento e Etologia Canina Os cães interagem com agentes artificiais (UMOs), mas não sabemos se os reconhecem como agentes sociais. O comportamento de ciúme surge quando uma relação importante é ameaçada por outro indivíduo, mas apenas quando o rival é social. Investigámos se os UMOs geram comportamento de ciúme nos cães. Testámos três grupos de 15 cães, cada grupo observou diferentes comportamentos do UMO: comportamento mecânico, não-social ou social. Posteriormente, o dono interagiu com o outro cão, o UMO e uma revista, enquanto ignorava a cobaia. Os cães demonstraram mais comportamento orientado ao rival e tentaram interromper a interação dono-rival mais vezes no caso do outro cão e do UMO comparado com a revista (principalmente no grupo do UMO Social). Porém, os cães mostraram menos comportamento dirigido ao dono e à interação no caso do UMO. Portanto, apesar de alguns elementos de comportamento de ciúme surgirem com o UMO, os resultados não são conclusivos.